Logistics platform strategies for freight technology-enabled smart services - Christoph Heinbach; Martin Schwemmer; Oliver Thomas (Adapting to the Future: How Digitalization Shapes Sustainable Logistics and Resilient Supply Chain Management. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 31, 2021)
Purpose: In this paper, the authors investigate logistics platform strategies in the road freight market through the analysis of business models of logistics service providers (LSPs) and freight technology providers (FTPs). The purpose of this paper is to gain knowledge of emerging freight technologies and to explore logistics platform strategies between LSPs and FTPs enabling smart services. Methodology: This paper follows an empirical analysis approach to study business models using the concept of Business Model DNA. To this end, the business models of 25 LSPs and 15 FTPs are investigated according to 55 business model patterns (BMPs). Subsequently, the authors conceptualize four logistics platform models to demonstrate how LSPs can manage nascent freight technologies. Findings: The authors argue that freight technology-enabled smart services can promote digital forwarding by logistics platform strategies. LSPs can make use of complementary service capabilities while FTPs can benefit from profound customer access and physical logistics resources. Originality: To the best of the authors' knowledge, no empirical research exists that consistently focuses on logistics platform strategies for freight technology-enabled smart services. The obtained insights in this study lead to the first contribution of digital platform strategies for road freight transportation in the sphere of digital logistics.
urn:nbn:de:gbv:830-882.0161825; hdl:10419/249608; https://econpapers.repec.org/RePEc:zbw:hiclpr:31
Keywords: 650; Innovation management; technology management